Effects of Methotrexate on Ovary: An Experimental Study on Albino Rat - Battan, Gulshan; Tandon, Rati; Vasenwala, Shaista M; Faruqi, Nafis Ahmad (Academia Anatomica International, 2017)
Background:Methotrexate is an anti-cancer drug but carries toxic effects on genital system and the study was conducted to find out the exact mechanism involved and to search for remedy. Methods: welve female albino rats 6 experimental and 6 control received methotrexate. [in former] and normal saline. [in latter], 1 mg/kg, intraperitoneally for 6 weeks. Results: H/E stained sections from ovary of experimental rat showed poorly developed Graafian follicles with loss of ova. There were follicular spaces in these rats with albuminous fluid and inflammatory cells. Granulosa lutein cells also showed degeneration due to inflammation. Cells were found to be smaller, shrunken, and irregular with vacuolated lighter colour cytoplasm. Conclusion: The drug is safer to be used in those patients who have completed their family.